Quantitative Evaluation of Antibiotics Use Trend in One Puskesmas in Bengkulu City: ATC/DDD and DU 90% Methods - Muslim, Zamharira; Amesta, Sonia; Susilo, Avrilya Iqoranny (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Irrational use of antibiotics results in decreased effectiveness of antibiotics due to inappropriate use of therapeutic doses or methods of use. This causes the bacteria to become resistant to antibiotic therapy. Periodic evaluation of antibiotic use is necessary. This study aims to evaluate the use of antibiotics quantitatively in one of the Puskesmas in Bengkulu City in 2021. This type of research is descriptive research. The sample used is an antibiotic prescription in 2021 and is taken by total sampling. This research uses the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) and Drugs Utilization 90% (DU 90%) methods. The results obtained were the number of prescriptions containing antibiotics as many as 1422 prescriptions (18.40%) of the total prescriptions (7730 prescriptions). The antibiotic prescriptions consisted of 1205 prescriptions for oral preparations and 217 prescriptions for topical preparations. There are 9 types of antibiotics used during 2021, namely Amoxicillin, Ciprofloxacin, Cefixime, Chloramphenicol, Gentamicin, Oxytetracycline, Levofloxacin, Tetracycline, and Tiamphenicol. The most widely used antibiotic was Amoxicillin (92.28%) with a DDDs per 1000 inhabitants per day value of 429.27 followed by Ciprofloxacin (5.06%) with a DDD value of 30.47. So it can be concluded that the most use of antibiotics in 2021 in one of the Puskesmas in Bengkulu City is Amoxicillin.